In silico research of anti-CHIKF phytoconstituent-based from Physalis peruviana leaves via molecular docking and dynamics analyses - Setiyowati, Putri Ayu Ika; Mahbubillah, M. Ainul; Aini, Nur Sofiatul; Rachmawati, Yuanita (Genbinesia Journal of Biology, 2023)
Chikungunya fever (CHIKF) is an infectious disease that has similar symptoms with dengue fever (DF). Several drugs have been offered to treat both dengue (DENV) and chikungunya virus (CHIKV). Investigating anti-CHIKF potential from nearby plants is one strategy to produce potential drug to reduce CHIKF in endemic countries. Physalis peruviana is one the promising object to be new anti-CHIKV drug candidate. This study aimed to analyze the anti-CHIKV agents from leaf parts of P. peruviana. Ligand and protein samples were collected from multiple sources. The phytoconstituents were evaluated their drug-likeness properties throughout SwissADME webservers. Selected ligands then docked via PyRX and measured the output by binding affinity. Visualization of the best outputs was carried out using BIOVIA Discovery Studio. CABS-flex was carried out to screen the RMSF of molecular dynamics activity of the best complex. The result showed that 1,2-benzenecarboxylic acid had the lowest binding affinity following suramin as control with -5.1 and -11.1 kcal/mol after targeting E2 domain protein of CHIKV. This led to the conclusion that 1,2-benzenecarboxylic acid could be forecast as predictive anti-CHIKF therapeutic candidate. Additional in vitro and in vivo studies are needed to validate this outcome.